On the Influence of Science Funding Policies on Business Sector R&D Activity - Rószkiewicz, Marta Magdalena (Equilibrium. Equilibrium. Quarterly Journal of Economics and Economic Policy, 2014)
The analysis focuses on assessing the impact of science and innovation policy on increasing business research activity, represented by the measure of business expenditure on research (BERD). The study concentrates on the impact of direct and indirect funding instruments. The effects of public intervention were examined basing on the pursued policy and the country’s level of innovativeness in 21 countries. In order to build aggregate variables of direct and indirect financial flows, the procedure of principal components was performed. Correlations between these variables and business sector activity were examined. The procedure of hierarchical clustering allowed to determine groups of countries which used similar policy instruments and experienced the same dynamics of BERD expenditures. The aim of such clustering was to highlight basic types of relations between the policy pursued and the activity of business sector. The study allowed to determine that direct funding has a significant effect on increasing BERD expenditures and is decreasing with the growing intensity of these outlays. The relation for indirect funding was found to be more complex. The generosity of country’s tax incentives for R&D was proved to be dependent on the level of innovativeness of business sector and was represented by an inverted U-shaped curve. The level of innovativeness was also found to have a stronger impact on business sector research activity than the policy pursued by a country. Basic recommendations on research funding policies were built based on the performed analysis.